M|G|∞ queue busy period with PME distribution - Ferreira, M. A. M. (Journal of Mathematics and Technology, 2013)
In this article it is shown that if the busy period of a\ M\left|G\right|∞ queue system is PME distributed, the service time is a random variable with a long-tail distribution. The result is obtained through Laplace transforms analysis.